(untitled) (Research, Society and Development, 2022)
In view of the challenges encountered in education, especially those posed by the ongoing SARS-CoV-2 pandemic and resulting school shutdowns, teachers and school administrators have looked for alternatives to conventional face-to-face teaching methods. This study aimed at advancing the teaching of chemistry by means of a contextualized and interdisciplinary approach integrating the curriculum topic “Solar System” to general chemistry concepts and theories. To this end, online and face-to-face classes, supported by a guidebook, were conducted about the subject matter in question at a public secondary school in Itacoatiara, AM, Brazil. The participating students responded to two questionnaires, an exploratory questionnaire and an evaluation questionnaire before and after the intervention, respectively. The guidebook was made available to participants both face-to-face and virtually (Google Classroom). The results suggest that the use of contextualization in classes about the solar system was capable of motivating the participants to learn chemistry concepts and theories. In addition, the results indicate that the students would like to experience other chemistry teaching methods that promote learning beyond the classroom.